Protein tyrosine phosphatase receptor type O (PTPRO) knockdown enhances the proliferative, invasive and angiogenic activities of trophoblast cells by suppressing ER resident protein 44 (ERp44) expression in preeclampsia. Issue 2 (20th December 2021) - Yang, Yang; Qiu, Xiaoxia; Wang, Fang
ABSTRACT: Preeclampsia (PE), a pregnancy-specific syndrome, is the primary cause of maternal mortality. This work was designed to investigate the specific functions of PTPRO/ ERp44 in the biological behaviors of trophoblast cells and elucidate the underlying molecular mechanism. Constructed siRNA-PTPRO and ERp44 overexpression plasmids were transfected into HTR-8/SVneo and JEG-3 cells for further functional experiments. Subsequently, the proliferation and invasion of trophoblast cells were identified by performing CCK-8, flow cytometry and transwell assay. In addition, tube formation assay was employed to estimate the angiogenic ability of HUVECs incubated with the conditioned media (CM) of HTR-8/SVneo or JEG-3 cells. Importantly, the interaction between PTPRO and ERp44 was analyzed through Co-IP. In the current investigation, it was discovered that downregulation of PTPRO notably facilitated the proliferation and invasion of trophoblast cells and induced a stronger in vitro angiogenesis. Moreover, PTPRO interacted with ERp44 to regulate ERp44 expression. ERp44 overexpression suppressed the proliferative, invasive and angiogenic activities of trophoblast cells. As a result, functions of PTPRO knockdown in the biological behaviors of trophoblast cells were partially abrogated upon elevation of ERp44. To sum up, this current research systematically evidenced that PTPRO could regulate the biological behaviors of trophoblast cells by modulating ERp44. Findings may contribute to a novel therapeutic strategy for PE.